Clinical efficacy and safety of achieving very low LDL-cholesterol concentrations with the PCSK9 inhibitor evolocumab: a prespecified secondary analysis of the FOURIER trial - Giugliano, Robert P; Pedersen, Terje R; Park, Jeong-Gun; De Ferrari, Gaetano M; Gaciong, Zbigniew A; Ceska, Richard; Toth, Kalman; Gouni-Berthold, Ioanna; Lopez-Miranda, Jose; Schiele, François; Mach, François; Ott, Brian R; et al. (The Lancet (British edition), 2017)
LDL cholesterol is a well established risk factor for atherosclerotic cardiovascular disease. How much one should or safely can lower this risk factor remains debated. We aimed to explore the relationship between progressively lower LDL-cholesterol concentrations achieved at 4 weeks and clinical efficacy and safety in the FOURIER trial of evolocumab, a monoclonal antibody to proprotein convertase subtilisin-kexin type 9 (PCSK9). In this prespecified secondary analysis of 25 982 patients from the randomised FOURIER trial, the relationship between achieved LDL-cholesterol concentration at 4 weeks and subsequent cardiovascular outcomes (primary endpoint was the composite of cardiovascular death, myocardial infarction, stroke, coronary revascularisation, or unstable angina; key secondary endpoint was the composite of cardiovascular death, myocardial infarction, or stroke) and ten prespecified safety events of interest was examined over a median of 2·2 years of follow-up. We used multivariable modelling to adjust for baseline factors associated with achieved LDL cholesterol. This trial is registered with ClinicalTrials.gov, number NCT01764633. Between Feb 8, 2013, and June 5, 2015, 27 564 patients were randomly assigned a treatment in the FOURIER study. 1025 (4%) patients did not have an LDL cholesterol measured at 4 weeks and 557 (2%) had already had a primary endpoint event or one of the ten prespecified safety events before the week-4 visit. From the remaining 25 982 patients (94% of those randomly assigned) 13 013 were assigned evolocumab and 12 969 were assigned placebo. 2669 (10%) of 25 982 patients achieved LDL-cholesterol concentrations of less than 0·5 mmol/L, 8003 (31%) patients achieved concentrations between 0·5 and less than 1·3 mmol/L, 3444 (13%) patients achieved concentrations between 1·3 and less than 1·8 mmol/L, 7471 (29%) patients achieved concentrations between 1·8 to less than 2·6 mmol/L, and 4395 (17%) patients achieved concentrations of 2·6 mmol/L or higher. There was a highly significant monotonic relationship between low LDL-cholesterol concentrations and lower risk of the primary and secondary efficacy composite endpoints extending to the bottom first percentile (LDL-cholesterol concentrations of less than 0·2 mmol/L; p=0·0012 for the primary endpoint, p=0·0001 for the secondary endpoint). Conversely, no significant association was observed between achieved LDL cholesterol and safety outcomes, either for all serious adverse events or any of the other nine prespecified safety events. There was a monotonic relationship between achieved LDL cholesterol and major cardiovascular outcomes down to LDL-cholesterol concentrations of less than 0·2 mmol/L. Conversely, there were no safety concerns with very low LDL-cholesterol concentrations over a median of 2·2 years. These data support further LDL-cholesterol lowering in patients with cardiovascular disease to well below current recommendations. Amgen.